2018
DOI: 10.3390/ijms19051293
|View full text |Cite
|
Sign up to set email alerts
|

Adropin Contributes to Anti-Atherosclerosis by Suppressing Monocyte-Endothelial Cell Adhesion and Smooth Muscle Cell Proliferation

Abstract: Adropin, a peptide hormone expressed in liver and brain, is known to improve insulin resistance and endothelial dysfunction. Serum levels of adropin are negatively associated with the severity of coronary artery disease. However, it remains unknown whether adropin could modulate atherogenesis. We assessed the effects of adropin on inflammatory molecule expression and human THP1 monocyte adhesion in human umbilical vein endothelial cells (HUVECs), foam cell formation in THP1 monocyte-derived macrophages, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 49 publications
5
101
0
1
Order By: Relevance
“…Of note, beneficial effects of adropin detected in vitro were confirmed by an in vivo study showing that adropin stimulates neovascularization via activation of eNOS kinase [46]. Concordantly, another study revealed that adropin has the ability to suppress THP1 monocyte adhesion to HUVEC cells induced by TNFα, suggesting an anti-inflammatory potential of adropin [47]. Moreover, in apolipoprotein E (Apoe) deficient mice (animal model of atherosclerosis [48]) synthetic adropin led to attenuation of atherosclerotic lesions and monocyte/macrophage infiltration in the aorta [47].…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 75%
See 1 more Smart Citation
“…Of note, beneficial effects of adropin detected in vitro were confirmed by an in vivo study showing that adropin stimulates neovascularization via activation of eNOS kinase [46]. Concordantly, another study revealed that adropin has the ability to suppress THP1 monocyte adhesion to HUVEC cells induced by TNFα, suggesting an anti-inflammatory potential of adropin [47]. Moreover, in apolipoprotein E (Apoe) deficient mice (animal model of atherosclerosis [48]) synthetic adropin led to attenuation of atherosclerotic lesions and monocyte/macrophage infiltration in the aorta [47].…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 75%
“…Concordantly, another study revealed that adropin has the ability to suppress THP1 monocyte adhesion to HUVEC cells induced by TNFα, suggesting an anti-inflammatory potential of adropin [47]. Moreover, in apolipoprotein E (Apoe) deficient mice (animal model of atherosclerosis [48]) synthetic adropin led to attenuation of atherosclerotic lesions and monocyte/macrophage infiltration in the aorta [47]. In the context of the cardiovascular system, adropin may modulate the patency of the blood-brain barrier [49].…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 93%
“…Therefore, activation of PPAR-γ may reduce macrophage infiltration and inflammation of adipose tissues. The study demonstrated that adropin regulates the anti-inflammatory or proinflammatory phenotypes of macrophages by up-regulating the expression of PPAR-γ [24]. Although, in current research, the reason for the tissue-specific effects of adropin on PPAR-γ expression is often unclear, PPAR-γ may be an important target for adropin to exert anti-inflammatory effects (Figure 2).…”
Section: Metabolic Disorders Caused By the Immune Regulation Of Adropinmentioning
confidence: 90%
“…On the one hand, as an endogenous vasodilator, NO plays a substantial role in maintaining the homeostasis of endothelial cells [31]; on the other hand, NO can exert immunomodulatory influences in inhibiting adhesion of monocytes and leukocytes to the endothelia [32]. Sato et al [24] demonstrated that adropin can inhibit TNF-α-induced adhesion of THP1 monocytes to endothelial cells in the process of atherosclerosis. With impeding monocyte-endothelial cell interactions, it can inhibit the inflammatory response of endothelial cells and monocytes/macrophages.…”
Section: Correlation Between Inhibition Of Inflammation By Adropin Anmentioning
confidence: 99%
See 1 more Smart Citation